Effect of a two-step fermentation method with rumen liquor on protein quality of wheat bran and rice bran to use as poultry feed. Issue 12 (December 2022) - Debi, Momota Rani; Wichert, Brigitta A.; Wolf, Petra; Liesegang, Annette
Abstract: The availability of high quality protein rich feed in many developing countries is limited as well as expensive. Low-quality agro-industrial by-products, i.e., rice bran (RB) and wheat bran (WB), are therefore used as poultry feed irrespective of their low protein content. The main objective of the present study was to improve the protein content and the amino acid profiles of these by-products through rumen liquor mixed fermentation process. A two-step fermentation of some agricultural by-products (e.g., WB and RB) was performed in a controlled environment for 3 h and 6 h. In the 1st and 2nd steps, feedstuff (brans), McDougall buffer as well as collected rumen liquor were mixed with following the proportion of 1:2:3, respectively. After fermentation, brans were dried at 100 °C in an oven. Dried sample were used to analyze the crude protein (CP) as well as amino acid (AA) content. In 1st and 2nd fermentation of the WB, CP content increased 3.3 ± 0.2% (3 h), 4.3 ± 0.2% (6 h) and 7.7 ± 0.1% (3 h), 8.5 ± 0.1% (6 h), respectively compared to control. On the other hand, RB protein content increased by 3.3 ± 0.1% (3 h), 0.8 ± 0.1% (6 h) and 7.3 ± 0.3% (3 h), 4.0 ± 0.1% (6 h) in the 1st and 2nd fermentation step, respectively compared to control. Majority of the AA increased compared to control during the 1st fermentation step for RB and WB. However, In WB, some of the AA did not show significant difference. A number of AA were decreased after the 2nd step for both RB and WB except Methionine, which increased in both steps. In 1st and 2nd steps, Methionine increased by 24.9 ± 5.1% (3 h), 25.9 ± 5.8% (6 h) for WB and 12.2 ± 3.2% (3 h), 13.0 ± 4.5% (6 h) for RB, respectively compared to control. In conclusion brans protein and amino acid quality optimization might be possible through methodical rumen liquor mixed fermentation process for better utilization as poultry diet. Abstract : Brans; Two-step fermentation; Protein; Essential amino acids; Poultry feed.